What Saint Paul really said : was Paul of Tarsus the real founder of Christianity? - Wright, N. T. (Nicholas Thomas) (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2014)
"In this book N.T. Wright provides a concise, authoritative account of the apostle Paul's contribution to the birth of Christianity. In exploring Paul's background and his teaching, Wright refutes the argument made by some scholars that it was Paul and not Jesus who founded Christianity. Rather, as Wright shows, Paul's gospel revolved around Jesus of Nazareth as Israel's Messiah and king, and Paul consistently pointed to the crucified and risen Jesus as the foundation of the church and Lord of all."--Back cover
Puzzling over Paul -- Saul the persecutor, Paul the convert -- Herald of the King -- Paul and Jesus -- Good news for the pagans -- Good news for Israel -- Justification and the Church -- God's renewed humanity -- Paul's gospel, then and now -- Paul, Jesus, and Christian origins
Based on various lectures given at various places and times
First American edition published 1997
Includes bibliographical references (pages 223-233)
Keywords: Paul, -- the Apostle, Saint; Bible. -- Theology; Christianity -- Origin; JUSTIFICATION AND THE CHURCH